1961
DOI: 10.1111/j.1749-6632.1961.tb20183.x
|View full text |Cite
|
Sign up to set email alerts
|

The Efferent Control of Afferent Signals Entering the Central Nervous System

Abstract: The centrifugal control of afferent transmission in central sensory stations, long suspected by the perceptive neuroanatomists Cajal,5 Brouwer,3 and Wallenberg,42 is now firmly established as the result of numerous experiments carried out during the last six years.Early as well as recent anatomical studies,2,3'5.6'33,34,4n,41 *42 have shown in the central nervous system the presence of efferent or centrifugal fibers projecting down to sensory synapses as low as those of the spinal cord, of the spinal fifth sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0
4

Year Published

1963
1963
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(20 citation statements)
references
References 13 publications
1
15
0
4
Order By: Relevance
“…The authors suggest that subcortical regions of the brain might be responsible for controlling the execution of motor tasks and the processing of music; in this case, little processing would need to take place for music to have its beneficial effects on affective responses. Furthermore, it has been indicated that music could not only activate one sensory region, but also reduce the activity in other sensory regions (Hernández‐Peón, Brust‐Carmona, Peñaloza‐Rojas, & Bach‐Y‐Rita, ), and these combined responses could be responsible for the positive effects of music on fatigue‐related symptoms and affective responses (Karageorghis & Priest, ). The present results are noticeably similar to those found by Jones et al () and Hutchinson et al (), and support the notion that music‐related interventions are facilitative strategies that modulate affective valence, attentional focus, and task performance during the execution of exhaustive or fatiguing motor tasks.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggest that subcortical regions of the brain might be responsible for controlling the execution of motor tasks and the processing of music; in this case, little processing would need to take place for music to have its beneficial effects on affective responses. Furthermore, it has been indicated that music could not only activate one sensory region, but also reduce the activity in other sensory regions (Hernández‐Peón, Brust‐Carmona, Peñaloza‐Rojas, & Bach‐Y‐Rita, ), and these combined responses could be responsible for the positive effects of music on fatigue‐related symptoms and affective responses (Karageorghis & Priest, ). The present results are noticeably similar to those found by Jones et al () and Hutchinson et al (), and support the notion that music‐related interventions are facilitative strategies that modulate affective valence, attentional focus, and task performance during the execution of exhaustive or fatiguing motor tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Por otro lado, el carácter de esfuerzo en las semanas con canciones de tempo musical elevado (>100 bpm) fue menor que en las semanas con canciones de tempo bajo (<100 bpm). En línea con las teorías de "percepción selectiva" de Broadbent (1958) y de "atención focalizada" de Hernández-Peon (1961), parace que el sistema nervioso centra la atención en la música como único estímulo, inhibiendo los demás envolventes durante la práctica deportiva y atenuando la sensación de cansancio (Copeland y Franks, 1991;Nideffer, 1976;Guillén y Ruiz-Alfonso, 2013;Hernández-Peon, 1961;Ju-Han y Jing-Horng Lu, 2013;Pennebaker y Lightner, 1980;Rejeski, 1985). Por lo tanto, aunque la música no cambia la fatiga producida al realizar los ejercicios, sí cambia la percepción del sujeto acerca de ésta.…”
Section: Discussionunclassified
“…Este posible efecto parece poder explicarse según las teorías de "percepción selectiva" (Broadbent, 1958) y de "atención focalizada" (Hernández-Peon, 1961), según las cuales el sistema nervioso puede atender únicamente a un estímulo (musical, en este caso) a expensas de discriminar el resto de estímulos envolventes (Copeland y Franks, 1991;Nideffer, 1976) atenuando la sensación de cansancio en el individuo (Guillén y Ruiz-Alfonso, 2013;Hernández-Peon, 1961;Ju-Han y Jing-Horng Lu, 2013;Pennebaker y Lightner, 1980). Rejeski (1985) también señala que la capacidad del sistema nervioso central es limitada y que solo es capaz de atender a un estímulo, por lo que, cuando una actividad física es acompañada por música, los estímulos que produce ésta pueden evitar las señales de retroalimentación relacionadas con el esfuerzo físico (Karageorghis y Priest, 2012).…”
Section: Música Y Carácter De Esfuerzo Percibidounclassified
“…Primeiramente os dados foram submetidos à estatística descritiva. -Peon et al (1961), o cérebro possui uma quantidade limitada de informações que podem ser processadas ao mesmo tempo e, a música, acabaria por inibir sensações "desagradáveis" resultante do exercício físico, atenuando a sensação de esforço do indivíduo. Essa teoria tem sido utilizada para explicar os efeitos da música durante o exercício físico (Karageorghis & Terry, 1997;Szmedra & Bacharach, 1998).…”
Section: Análise Estatísticaunclassified